Strengthening production capacity through financial management and digital marketing: Evidence from PKK Women’s groups in Matara Village, Merauke - Intan Farida Khasanah; Prima Lestari Situmorang; Hermanto Tinambunan; Desmina Kristiani Hutabarat; Najdah Thalib; A. Abdullah; Khoirul An’am; Adela Anita; Gabriel Gloria Ohee; Seven Marganda Bako; Nurul Uswatun Hasanah (Privietlab, 2026)
This community service activity aimed to improve the production capacity, financial management literacy, and digital marketing skills among members of the Family Welfare Empowerment group in Matara Village by developing fish nuggets as a value-added processed product utilizing local fisheries potential. The program was implemented using a participatory approach through educational and training activities, including program socialization, fish nugget production training, simple financial management training, and digital marketing training. The activities were conducted at the Matara Village Hall and involved 20 participants from the local community group. The results indicated a significant improvement in participants understanding of hygienic production techniques, their ability to maintain simple financial records, and their use of social media as a platform for product promotion. The integration of production training, financial management, and digital marketing also encouraged the development of household enterprises utilizing fisheries products and expanded opportunities for marketing processed products. This activity contributed to strengthening the capacity of community-based enterprises and supported the development of economic independence through the utilization of local resource potential in Matara Village.